Selective synthesis of propenyl‐branched diunsaturated fatty esters via catalytic codimerization of ethyl linoleate and propylene. Issue 1 (6th August 2015) - Erb, Benjamin; Dierker, Markus; Ohlmann, Dominik M.; Gooßen, Lukas J.
Abstract : A bimetallic catalyst system consisting of RhCl3 and Pd(MeCN)2 Cl2 efficiently promotes the conversion of ethyl linoleate selectively to mono‐propenylated diunsaturated products. The reaction proceeds in high yields under mild conditions. The key advantage of the new process is that it is based on the readily available linoleate rather than a preformed conjuenic acid ester. Practical applications: The new protocol opens up a high yielding and environmentally friendly method for the introduction of side chains with a defined length into fatty acid derivatives. The products are of profound potential interest for industrial applications, e.g., in lubricants, cosmetics, plastics, and coatings, as branched fatty acids are known to have a lower solidifying point and viscosity and an increased solubility than their linear counterparts. Rh/Pd‐catalyzed selective conversion of ethyl linoleate to mono‐propenylated diunsaturated products under mild conditions. Abstract : Rh/Pd‐catalyzed selective conversion of ethyl linoleate to mono‐propenylated diunsaturated products under mild conditions.